Virgin : poems - Sotelo, Analicia (Minneapolis, Minnesota : Milkweed Editions, 2018)
Selected by Ross Gay as winner of the inaugural Jake Adam York Prize, Analicia Sotelo's debut collection of poems is a vivid portrait of the artist as a young woman. In Virgin, Sotelo walks the line between autobiography and mythmaking, offering up identities like dishes at a feast. These poems devour and complicate tropes of femininity'of naivetE, of careless abandon'before sharply exploring the intelligence and fortitude of women, how 'far & wide, / how dark & deep / this frigid female mind can go.' A schoolgirl hopelessly in love. A daughter abandoned by her father. A seeming innocent in a cherry-red cardigan, lurking at the margins of a Texas barbeque. A contemporary Ariadne with her monstrous Theseus. A writer with a penchant for metaphor and a character who thwarts her own best efforts. 'A Mexican American fascinator.' At every step, Sotelo's poems seduce with history, folklore, and sensory detail'grilled meat, golden habaNeros, and burnt sugar'before delivering clear-eyed and eviscerating insights into power, deceit, relationships, and ourselves. Here is what it means to love someone without truly understanding them. Here is what it means to be cruel. And here is what it means to become an artist, of words and of the self. Blistering and gorgeous, Virgin is an audacious act of imaginative self-mythology from one of our most promising young poets.
Intro -- Cover -- Title Page -- Copyright -- Dedication -- Contents -- Do You Speak Virgin? -- Taste -- Summer Barbecue with Two Men -- A Little Charm -- You Really Killed That '80s Love Song -- Expiration Date -- Apologia over Marinated Lamb -- Purgatory Tastes Like Eggs -- Revelation -- South Texas Persephone -- Revelation at the All-Girls School -- Private Property -- Philosopher King -- I'm Trying to Write a Poem about a Virgin and It's Awful -- Humiliation -- Trauma with Damp Stairwell -- Trauma with Haberdashery -- Trauma with White Agnostic Male -- Trauma with a Second Chance at Humiliation -- Pastoral -- My Father &amp -- Dalí Do Not Agree -- My Father &amp -- de Chirico Asleep on Chairs of Burnt Umber -- Picnic Pastoral (with Dark-Skinned Father) -- My Father Lost in a Game of Chess -- Father Fragments (or, Yellow Ochre) -- Myth -- Ariadne Discusses Theseus in Relation to the Minotaur -- Ariadne's Guide to Getting a Man -- Death Wish -- Theseus at the Naxos Apartment Complex, 6 a.m. -- Ariadne at the Naxos Apartment Complex, 10 a.m. -- Ariadne Plays the Physician -- Parable -- My Mother as the Voice of Kahlo -- The Minotaur Invents the Circumstances of His Birth -- My Mother as the Face of God -- The Minotaur's Letter to Ariadne -- Separation Anxiety -- My Mother &amp -- the Parable of the Lemons -- Rest Cure -- Fast Track -- The Single Girl's Rest Cure -- My English Victorian Dating Troubles -- The Ariadne Year -- Acknowledgments -- About the Author.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: American poetry -- 21st century; LITERARY CRITICISM / Poetry; American poetry; 2000-2099; Poetry (Poetic Works By One Author); Poetry